2017
DOI: 10.1111/rda.12932
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplemental conjugated linoleic acids (CLA) on fresh and post‐thaw sperm quality of Holstein bulls

Abstract: This study was designed to investigate the effects of feeding-protected conjugated linoleic acid (CLA) on the semen production and sperm freezability in Holstein bulls. Twelve bulls were randomly assigned to two groups (n = 6 per group). Bulls received the normal diet (control group) or the normal diet top-dressed with 50 g of CLA (treated group) for 10 weeks. The control group received 40 g/day calcium soap of fatty acid. Fresh and post-thaw semen quality was assessed on ejaculates collected at the 0, 4, 6, 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…The current results are in agreement with studies in ruminants (Masoudi et al, 2016;Tran et al, 2016) and humans (Vireque et al, 2016;Ferramosca et al, 2017). However, other researchers reported different results (Mourvaki et al, 2010;Karimi et al, 2017). Khoshvaght et al (2016) concluded that feeding FO could improve the quality of fresh and frozen thawed semen by altering the sperm membrane fatty acid composition.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The current results are in agreement with studies in ruminants (Masoudi et al, 2016;Tran et al, 2016) and humans (Vireque et al, 2016;Ferramosca et al, 2017). However, other researchers reported different results (Mourvaki et al, 2010;Karimi et al, 2017). Khoshvaght et al (2016) concluded that feeding FO could improve the quality of fresh and frozen thawed semen by altering the sperm membrane fatty acid composition.…”
Section: Discussionsupporting
confidence: 90%
“…Based on the current results, feeding the rams with the addition of FO and PF could increase the seminal volume compared with that of the control, but it did not have significant effects on sperm concentration. Karimi et al (2017) showed that CLA could not increase bull semen volume and spermatozoa concentration. A probable reason or mechanism for seminal volume increasing with PUFAs is the synthesis and secretion of seminal plasma (Rooke et al, 2001;Khoshvaght et al, 2016).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A similar result was also observed by Karimi et al (59) in Holstein bulls. Evaluating the effect of CLA supplementation in the diet on the quality and freezability of sperm, the authors did not observe the effect of CLA on semen volume, sperm concentration and total sperm production (p> 0.05).…”
Section: Effect Of Cla Supplementation On Semen Cryopreservationsupporting
confidence: 90%